Optimasi Proses Pembuatan MOCAF dengan Metode Taguchi - Fathur Rizky; Didiek Hermanuadi (Politeknik Negeri Jember, 2023)
MOCAF or modified cassava flour, is one of the starch products that can be used for food products. The research method used was Taguchi experimental design to determine the optimum conditions by varying the factors in the process of making MOCAF. The analysis used was the signal-to-noise ratio proposed by Taguchi. The design of the Taguchi parameters used was an Orthogonal Array with 3 levels and 3 factors. Factors included the fermentation time of 12 hours, 18 hours, and 24 hours, then the H2O2 concentration varied by 1%, 5%, and 10%, and exposure to UV-C for 0 minutes, 5 minutes, and 10 minutes. Parameters observed were moisture content, ash content, fat content, swelling power, WHC, amylose, amylopectin, baking expansion, and brightness. It can be concluded that the optimum formulation for MOCAF based on data analysis and SNR graphics is the Baking Expansion parameter with 24 hours of fermentation, 10% H2O2 concentration, and 5 minutes of UV-C exposure.